University of Al-Qarawiyyin: A Bridge of Scientific Glory from Islam to the World (A Study of Islamic Civilization in the 9th Century AD) - Hudaini, Mumtasya; Khotimah , Husnul; Anam, Ahmad Qomarul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The University of Al-Qarawiyyin in Fez, Morocco, established in 859 AD during the 9th century, is recognized as the oldest continuously operating higher education institution in the world. Its existence reflects the Islamic world's commitment to elevating knowledge as a foundational pillar of civilization building. This study aims to examine the significant role of this university in laying the groundwork for an academic system that later inspired the model of modern universities in Europe.This article is written using the library research method with a historical-analytical approach. The main focus of the study is to trace the journey of the University of Al-Qarawiyyin and its influence in shaping the global educational system. The findings reveal that the University of Al-Qarawiyyin served not only as a center for Islamic learning but also as a space for intercultural and intellectual exchange. The university introduced several key concepts such as open scholarly discussions, the scientific certification system through ijazah, and a curriculum-based educational model.With its far-reaching contributions, the University of Al-Qarawiyyin stands as concrete evidence of the vital role Islamic civilization has played in the development of education and global knowledge to this day.